A grounded theory of regaining normalcy and reintegration of women with obstetric fistula in Kenya - Anne M. Khisa; Isaac K. Nyamongo; Grace M. Omoni; Rachel F. Spitzer (BMC, 2019)
Abstract Background Obstetric fistula is a reproductive health problem causing immense suffering to 1% of women in Kenya that is formed as sequelae of prolonged obstructed labour. It is a chronic illness that disrupts women lives, causing stigma and isolation. Fistula illness often introduces a crisis in women's life begetting feelings of shame and serious disruption to their social, psychological, physical and economic lives, in addition to dealing with moral and hygiene challenges. Currently, women undergo free of charge surgery at vesicovaginal fistula (VVF) camps held in national referral hospitals and dedicated fistula centres generating a significant pool of women who have undergone surgery and are ready to regain normal lives. Objective The purpose of this study was to explore experiences of women immersing back into communities and their return to normalcy after surgery in three VVF repair centres in Kenya. We set out to answer the question: what strategies improve obstetric fistula patients' reintegration process? Methods We used grounded theory methodology to capture the reintegration and regaining normalcy experiences of women after surgery. Narrative interviews were held with 60 women during community follow-up visits in their homes after 6-19 months postoperatively. Grounded theory processes of theoretical sampling, repeated measurement; constant comparative coding in three stage open, axial and selective coding; memoing, reflexivity and positionality were applied. Emergent themes helped generate a grounded theory of reintegration and regaining normalcy for fistula patients. Results To regain normal healthy lives, women respond to fistula illness by seeking surgery.. After surgery, four possible outcomes of the reintegration process present; reintegration fully or partially back into their previous communities, not reintegrated or newly integrating away from previous social and family settings. The reintegration statuses point to the diversity outcomes of care for fistula patients and the necessity of tailoring treatment programs to cater for individual patient needs. Conclusion The emerging substantive theory on the process of reintegration and regaining normalcy for fistula patients is presented. The study findings have implications for fistula care, training and policy regarding women's health, suggesting a model of care that encompasses physical, social, economic and psychological aspects of care after surgery and discharge.